Peran Orang Tua Dalam Pembelajaran Pada Masa Pandemic Covid -19 Di SD Negeri 1 Tobelo Kabupaten Halmahera Utara - Warye, Juliyarti; Syahril Muhammad; Sulfi Abdul Haji (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This research aims to determine the role of parents in learning during the Covid-19 pandemic at SD Negeri 1 Tobelo, North Halmahera Regency and to find out parents' strategies for providing guidance to children when studying during the Covid-19 pandemic. This research method is descriptive qualitative using the Snowball technique. . This research analysis is data reduction, data presentation and conclusions. The research results show the role of parents in the child's learning process during study from home. The role of parents is also very necessary to provide education to children who do not really understand about the Covid-19 pandemic which is currently endemic and is forcing people to stay at home, study from home, worship and work from home. In principle, so far apart from parents, there are also teachers or even peers who carry out this role. For now, it is almost certain that this role will only be carried out by parents or family at home, so there must be more strengthening, sensitivity and patience from parents in implementing distance education for early childhood children at home. The existence of learning activities at home also has benefits for children and their parents. This government policy regarding online learning makes us all aware of the importance of learning technology and using technology positively.